Reflections of a Rotten Nature: Hegel, Lacan, and Material Negativity - Johnston, Adrian (Filozofski vestnik, 2013)
Herein, I distinguish between two basic, fundamental conceptions of the sorts of negativity associated with subjectivity throughout modern European philosophy up to the present: on the one hand, a mystical vision in which the unexplained explainer of a mysterious nothingness is appealed to as a ground-zero given; on the other hand, a materialist idea according to which the real privative causes of absences and antagonisms are internally generated out of precisely specifiable natural and human historical processes involving accumulations of multitudes of concrete elements and features. Arguing against the former as complacently resting upon the dogma of a “myth of the non-given” (to borrow a phrase from Wilfrid Sellars so as to refer to the notion of the factical givenness of negativity as itself non-given), I plead for the latter and sketch a dialectical-speculative “more is less” dynamic in which surpluses of positivity immanently give rise to negativities. This dynamic is an essential part of a non-reductive materialism including within itself lacks and conflicts as causally efficacious factors. I flesh out these lines of thought through reinterpretations of the transition from the organic to the anthropological in Hegel as well as the mirror stage as an account of ego- and subject-formation in Lacan.